ANALISIS POTENSI EKSPOR HASIL-HASIL PERTANIAN DI KABUPATEN KARO - Ita Marlin Bukit (Departemen Ekonomi Pembangunan USU, 2013)
This research aims to analyze export potency of agricultural products and their demand in Karo. This research uses secondary data in time series that is the number of agricultural commodity production Karo, the volume and value of exports of agricultural commodities Karo 2002-2010. It is analyzed by Location Quotient (LQ) method, Typology Klassen, Shift Share Analysis and descriptive analysis. Results of Location Quotient (LQ), Typology Klassen, and Shift Share Analysis shows that commodities that have export potential, bases, forward and grow rapidly are cabbage, carrots, onions and orange. Commodities with the highest level of demand each year is the cabbage and potatoes respectively 48929.59 and 27227.28 tons tons in 2009.Keywords: export, commodity, Location Quotient (LQ), Typology Klassen, Shift Share